A novel frameshift variant in SON causes Zhu‐Tokita‐Takenouchi‐Kim Syndrome. Issue 8 (14th April 2020) - Tan, Ya; Duan, Ling; Yang, Kai; Liu, Qian; Wang, Jing; Dong, Zhe; Li, Zhi; He, Yiwen; Yan, Yousheng; Lin, Li
Abstract: Background: Zhu‐Tokita‐Takenouchi‐Kim syndrome is a severe multisystem developmental disorder characterized by intellectual disability, developmental delay, malformations of the cerebral cortex, epilepsy, vision problems, musculoskeletal abnormalities, and congenital malformations. This syndrome is caused by heterozygous pathogenic variants in the SON gene at chromosome 21q22.1. Objectives: The aim of this study was to investigate the pathogenesis of a 4‐year‐old Chinese child who displayed severe intellectual disability, delayed psychomotor development, and facial dysmorphism. Methods: A sequential detection including chromosome karyotyping, chromosome microarray analysis (CMA), and whole‐exome sequencing (WES) was performed on this child. The familial verification of WES result was conducted by Sanger sequencing. Results: A de novo frameshift variant SON : c.5230delC (p.Arg1744ValfsTer29) was identified in the proband. The identical variant was not found in his family members. The frequencies of this variant in gnomAD/gnomAD_EAS databases were both none. Conclusions: This study substantiates that SON : c.5230delC (p.Arg1744ValfsTer29) is a pathogenic variant of Zhu‐Tokita‐Takenouchi‐Kim syndrome and it is the first time to report Zhu‐Tokita‐Takenouchi‐Kim syndrome in China.